Exploiting Single-Cell Tools in Gene and Cell Therapy - Bode, Daniel; Cull, Alyssa H.; Rubio-Lara, Juan A.; Kent, David G. (Frontiers in Immunology, 2021)
Single cell molecular tools have been developed at an incredible pace over the last five years as sequencing costs continue to drop and numerous molecular assays have been coupled to sequencing readouts. This rapid period of technological development has facilitated the delineation of individual molecular characteristics including the genome, transcriptome, epigenome, and proteome of individual cells, leading to an unprecedented resolution of the molecular networks governing complex biological systems. The immense power of single cell molecular screens has been particularly highlighted through work in systems where cellular heterogeneity is a key feature, such as stem cell biology, immunology, and tumor cell biology. Single cell -omics technologies have already contributed to the identification of novel disease biomarkers, cellular subsets, therapeutic targets and diagnostics, many of which would have been undetectable by bulk sequencing approaches. More recently, efforts to integrate single cell multi-omics with single cell functional output and/or physical location have been challenging but have led to substantial advances. Perhaps most excitingly, there are emerging opportunities to reach beyond the description of static cellular states with recent advances in modulation of cells through CRISPR technology, in particular with the development of base editors which greatly raises the prospect of cell and gene therapies. In this review, we provide a brief overview of emerging single cell technologies and discuss current developments in integrating single cell molecular screens and performing single cell multi-omics for clinical applications. We also discuss how single cell molecular assays can be usefully combined with functional data to unpick the mechanism of cellular decision-making. Finally, we will reflect upon the introduction of spatial transcriptomics and proteomics, its complementary role with single cell RNA sequencing (scRNA-seq) and potential application in cellular and gene therapy.